1991
DOI: 10.1128/mcb.11.5.2629
|View full text |Cite
|
Sign up to set email alerts
|

The yeast homolog to mouse Tcp-1 affects microtubule-mediated processes.

Abstract: A Saccharomyces cerevisiae homolog to Drosophila melanogaster and mouse Tcp-1 encoding taiDless complex polypeptide 1 (TCP1) has been identified, sequenced, and mapped. The mouse t complex and many of its unusual properties have attracted the attention of geneticists for nearly 60 years (11,12,20,60). t alleles were first discovered by their interaction with a dominant T-locus mutation to produce a tailless phenotype in double heterozygous T/t animals. Heterozygous T/+ animals have a short tail, and homozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(120 citation statements)
references
References 82 publications
(61 reference statements)
8
112
0
Order By: Relevance
“…There are previous reports that HSP60s in bacteria and mitochondria, which form group I chaperonins, are membrane associated (33)(34)(35)(36)(37). There are also reports that the HSP60-related TCP1s in eukarya, which form group II chaperonins (known as CCT or TriC), are membrane associated (38)(39)(40)(41). We recently discovered that in human red blood cells TCP1 is predominantly cytoplasmic under normal conditions, but after heat treatment it relocates to the membrane (C. T. Wagner, I. Y. Lu, M. H. Hoffman, W. Q.…”
Section: Discussionmentioning
confidence: 99%
“…There are previous reports that HSP60s in bacteria and mitochondria, which form group I chaperonins, are membrane associated (33)(34)(35)(36)(37). There are also reports that the HSP60-related TCP1s in eukarya, which form group II chaperonins (known as CCT or TriC), are membrane associated (38)(39)(40)(41). We recently discovered that in human red blood cells TCP1 is predominantly cytoplasmic under normal conditions, but after heat treatment it relocates to the membrane (C. T. Wagner, I. Y. Lu, M. H. Hoffman, W. Q.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to the cloning of the mouse TCPl gene (Willison et al, 1986), related proteins from Drosophilu (Ursic and Ganetzky, 1988) and S. cerevisiae (Ursic and Culbertson, 1991) were reported. The unexpected finding that TF55, an abundant protein of the thermophilic bacterium Sulfolobus shibatue, had not only the structural and functional hallmarks of a typical chaperonin but also had a very strong sequence similarity to TCPl lent support to the initial suggestion that TCPl might be a cytoplasmic chaperonin (Trent et al, 1991 In yeast, TCPl is essential for growth ; temperature-sensitive mutants show aberrant mitotic spindle formation (Ursic and Culbertson, 1991). Two independent studies demonstrated that TCPl plays a role in the biogenesis of tubulin and actin (Gao et al, 1992;Yaffe et al, 1992).…”
Section: Cytosolic Hsp60mentioning
confidence: 99%
“…Other mutants have been identified that also exhibit a nuclear migration defect (Watts et al, 1987;Berlin et al, 1990;Kormanec et al, 1991;Ursic and Culbertson, 1991;McConnell and Yaffe, 1992). The specific role of these genes in nuclear migration is not known and in all cases except numl the nuclear migration defect is only one trait of a more complex phenotype.…”
mentioning
confidence: 99%